The Impacts of Relational Norms and Relationship Quality on Franchise Firm’s Performance: The empirical of Malaysian Franchisee - Khairol Anuar Ishak; Nazlina Zakaria; Mohamad Khairi Ishak (International Journal of Supply Chain Management, 2018)
Franchising is one of the best way for expanding a business in the competitive industry and global market. Franchising industries are growing rapidly in most countries and have contributed to the growth of gross domestic product. This study adopts a quantitative approach, applying a cross-sectional study. This study attempts to examine empirically relational mechanisms which may influence the relationship quality and business performance in franchising relationship from franchisees perspective. The findings reveal that relational mechanisms are crucial in affecting franchisee relationship quality. The results provide strong evidence that franchisee relationship quality is found to significantly affect business performance in the franchise system.